2018
DOI: 10.5414/cp203180
|View full text |Cite
|
Sign up to set email alerts
|

Concomitant administration of candesartan cilexetil in patients on paclitaxel and carboplatin combination therapy increases risk of severe neutropenia

Abstract: Our data suggest that a drug-drug interaction between candesartan cilexetil and TC therapy is probable. Unlike with other ARBs, the possible increased risk for development of severe neutropenia should be taken into account when prescribing candesartan cilexetil in combination with TC therapy.
.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…Previously, we performed a comprehensive retrospective analysis of concomitant medications to identify potential risk factors for chemotherapy-induced severe neutropenia in patients administered paclitaxel plus carboplatin combination (TC) therapy. We found that concomitant use of candesartan cilexetil, unlike that of other angiotensin receptor blockers, could result in severe neutropenia (Katsube et al, 2018). Candesartan cilexetil, an angiotensin II receptor blocker, is commonly administered for the treatment of hypertension.…”
mentioning
confidence: 92%
“…Previously, we performed a comprehensive retrospective analysis of concomitant medications to identify potential risk factors for chemotherapy-induced severe neutropenia in patients administered paclitaxel plus carboplatin combination (TC) therapy. We found that concomitant use of candesartan cilexetil, unlike that of other angiotensin receptor blockers, could result in severe neutropenia (Katsube et al, 2018). Candesartan cilexetil, an angiotensin II receptor blocker, is commonly administered for the treatment of hypertension.…”
mentioning
confidence: 92%